HIV AND AIDS AND THE CHALLENGE TO CHRISTIAN MINISTRY: PROPOSING A CHRISTIAN ABC MODEL FOR HIV AND AIDS PREVENTION - Abraham, Thomas (Asian Horizons, 2019)
This study focuses on the reality and the consequences of Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) and proposes a strategic communication method for preventing HIV and AIDS globally. Perhaps, the number of people infected and affected with this reality is increasing day by day and the situation is becoming more complex every year. It is an established fact that the problem has gone beyond medical confines. HIV and AIDS has permeated all strata of human situations and many people lose their life as the consequences. This study would help people understand the seriousness of this issue, various ethical issues involved in it, and in particular the issue of justice in relation to HIV and AIDS and the role of the Church to address this situation biblically, theologically, ethically and pastorally. This study also attempts to analyse in depth issues like stigma and discrimination, and meaning and purpose of human sexuality. The main purpose of this study is to propose a new model of ABC, that is, ‘Abstinence, Be faithful with one partner and Communicating good sex to people of all age group,’ for preventing HIV and AIDS. It is a critique of the existing Ugandan model of ABC, where ‘C’ stands for Condom use. Since HIV spreads mainly through sexual route, behavioural change is probably the most effective way to control the transmission of HIV. This study is limited to the Christian response to HIV and AIDS on the biblical and theological basis.